Alternative herbal medicine for hemorrhoids, Effect of Arum maculatum on the quality of life of patients: A randomized controlled trial - Zisis, Serafeim; Giannakou, Konstantinos; Lavranos, Giagkos; Lamnisos, Demetris (My University, 2019)
Hemorrhoids is a common disorder and a leading cause of rectal bleeding, with unpleasant discomfort and pain for the patient. Medication and surgery are the standard treatments of hemorrhoids. In this study, we are investigating an alternative herbal treatment of hemorrhoids using the Arum maculatum L. (Araceae). A randomized controlled trial was conducted with a test treatment period of 2 weeks using a sample of 53 diagnosed patients from Greece to assess the efficacy of Arum maculatum in treating symptomatic hemorrhoids. The patients randomly assigned to consume a liquid mixture of Arum maculatum or a standard antihemorrhoid cream. The primary outcome was the health-related quality of life measured by the SF-36 health survey at the baseline and 2 weeks after the end of treatment. The mixed ANOVA statistical method was used to compare the groups. Participants in the treatment group had significantly greater improvement in all measures of the SF-36. Particularly the treatment effect for the physical health summary was 5.0 [95% confidence interval (CI): 0.9-9.1] while for the mental health summary was 4.7 (95% CI: 1.3-8.0). This trial shows that treatment with Arum maculatum improves the quality of life of patients with hemorrhoids, but further studies are needed to confirm these results.
Keywords: Alternative herbal medicine; Arum maculatum; Hemorrhoids; Quality of life; Randomized controlled trial